Does E-Government Improve Government Capacity? Evidence from Tax Compliance Costs, Tax Revenue, and Public Procurement Competitiveness - Kochanova, Anna (Published by Oxford University Press on behalf of the World Bank, 2021)
Using cross-country data on e-government systems, this paper analyzes whether e-filing of taxes and e-procurement implementation improves the capacity of governments to raise and spend fiscal resources through lowering tax compliance costs, improving tax collection and public procurement competitiveness, and reducing corruption. Adopting e-filing systems reduces tax compliance costs as measured by the time to prepare and pay taxes, the likelihood and frequency of firms being visited by a tax official, and the perception of tax administration as an obstacle to firms’ operation and growth. E-filing is also associated with a moderate increase in the income tax revenue to GDP ratio. The results for e-procurement are weaker, with the number of firms securing or attempting to secure a government contract increasing only in countries with higher levels of development and better institutions. There is no strong relationship between e-government and corruption.